Analysis of Service Quality Using Potential “Gain in Value” Method in Outpatient Polyclinic of X Hospital in Bali - Wijaya, I Wayan Septa; Rosita, Ni Putu Indah (CV. Global Health Science Group, 2024)
Private hospitals continue strive to improve patient satisfaction. In measuring the level of satisfaction of hospital patients, currently the IPA (Importance-Performance Analysis) method can be used. Even though the IPA score is high, in reality there are still complaints from people who are undergoing outpatient care. This is because the hospital has not prioritized what services need to be repaired and improved. The purpose of this research is to find out which attributes need to be prioritized in improving hospital services. This study uses Potential Gain in Customer Value (PGCV) method. Data were collected through questionnaires distributed to 30 patients undergoing outpatient care. Respondents were randomly selected from various age groups and backgrounds. Subsequently, the data were analyzed using the PGCV method to identify which attributes have the highest potential value gain. The research findings indicate that the attribute requiring improvement is